2017
DOI: 10.1590/0102-311x00043016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of referral letters written by general practitioners: a cross-sectional study in rural Iran

Abstract: Establishing effective communication between general practitioners (GPs) and medical specialists is a key component of the referral system. Written communication between GPs and medical specialists is the most common communication tool. This study was conducted to evaluate quality (information content) of the referral letters written by GPs and addressed to gynecologists and cardiologists. We evaluated quality of the referral letters through a cross-sectional study in the villages of Sarab city, located in Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…For example, reports from both HCPs and patients revealed that that documented information was often provided in the form of minimal, handwritten notes on papers provided for other purposes (eg, prescription cards). These findings reflect results from other LMIC studies that have evidenced the exchange of poor-quality referral documents 14 37–39. However, the current study also evidenced patient reports of not being provided with any documented information during referrals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, reports from both HCPs and patients revealed that that documented information was often provided in the form of minimal, handwritten notes on papers provided for other purposes (eg, prescription cards). These findings reflect results from other LMIC studies that have evidenced the exchange of poor-quality referral documents 14 37–39. However, the current study also evidenced patient reports of not being provided with any documented information during referrals.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the implementation of structured documentation, systems and training is urgently required to manage critical care transitions such as referrals, transfers and discharge. Research from both HIC and LMIC settings has proven that such interventions can improve the continuity and safety of care 4 17 37 49. Regarding future steps, during HCP interviews it was reported that public healthcare facilities in Kerala will be transitioning to computerised ‘e-health’ information systems.…”
Section: Discussionmentioning
confidence: 99%
“…General practitioners (GP) play a key role in primary healthcare in Iran (1). They act as gatekeepers who identify the needs of their patients and decide on the health services required for the better management of their complications (2).…”
Section: Introductionmentioning
confidence: 99%
“…A good referral should include the patient's biography, such as age, gender, tribe, religion, occupation, medical history, the reason for the referral, interventions or treatments received, and the clinical diagnosis [5] [6]. An effective referral system plays a critical role in achieving good and sustainable healthcare delivery in Nigeria.…”
Section: Introductionmentioning
confidence: 99%